Determining the Degree of Fuzzy Regularity of a String - Kostanyan, Armen H. (Mathematical Problems of Computer Science, 2021)
The paper deals with the issue of determining the degree of fuzzy regularity of a crisp string. It is assumed that the concept of fuzzy regularity is formalized by a pattern given as a finite automaton with fuzzy properties of alphabet characters on transitions. Proceeding from this, we replace the problem of determining the degree of fuzzy regularity of a crisp string with the problem of determining the degree of belonging of such a string to the language of the corresponding automaton and propose an effective method for solving it using the dynamic programming approach. The solution to the considered problem makes it possible to fuzzify the set of strings in a given alphabet based on a pattern defining fuzzy regularity. This work is a continuation of the author’s previous works related to finding occurrences of a fuzzy pattern in the text. It may have applications in the field of pattern recognition, data clustering, bio-informatics, etc.